CALCINATION ON Ca-Mg-Al HYDROTALCITE FROM BRINE WATER AND ITS CHARACTERIZATION - Heraldy, Eddy; Nugrahaningtyas, Khoirina Dwi; Heriyanto, Heriyanto (ALCHEMY Jurnal Penelitian Kimia, 2017)
The study of calcination at 450 ºC on Ca-Mg-Al-hydrotalcite synthesized from brine water has been investigated. Characterization by XRD shows that Ca-Mg-Al hydrotalcite compound has found hydrotalcite phase and another phase such as Mg(OH)2, Al(OH)3 and CaCO3. These results are confirmed by the presence of hydroxyl groups (-O-H), M-O and M-OH groups (M is Mg, Ca and Al) at wavenumber region around     3463,34 cm-1; 447,50 cm-1; 536,62 cm-1and 786,99 cm-1. The calcination on Ca-Mg-Al hydrotalcite at 450 ºC affected change in the structure become a metal oxide such as MgO, CaO, Al2O3, MgAl2O4, and CaCO3. These results are confirmed from decreasing on the absorption peak of M-OH group at wavenumbers around 536,62 cm-1and 786,99 cm-1 and widening of the absorption region at 447,5 - 857,4 cm-1. Consequently, the calcination treatment successfully increased the surface area of Ca-Mg-Al hydrotalcite compounds from 97.4 m2/g to 156.826 m2/g. Morphology of Ca-Mg-Al hydrotalcite underwent changes the shape from a big to be a small form. Thermal analysis results showed changes in the structure of Ca-Mg-Al hydrotalcite into oxides begin at a temperature of 210 ºC and become oxide completely after the temperature reaches 420 ºC.